The Effect of Service Quality Customer Satisfaction at Galang Post Office - Chatarine Sela Sinaga (Journal of Economics and Business (JECOMBI), 2022)
This study aims to find out the Effect of Service Quality on Customer Satisfaction at Galang Post Office. The samples used in this study were customers of Galang Post Office, aged 16 years to 69 years, had used the services of Galang Post Office. The number of samples used based on the size of the population, then the number of samples can be as many as 55 people. The results of this study showed that free variables, namely Service Quality (X), affect Customer Satisfaction (Y) thatuses n Galang Post Office services. The results of this study showed that Quality of Service has an influence of 68.2%on Customer Satisfaction of Galang Post Office.